Tarjetas de crédito en el Perú: análisis de los factores socioeconómicos y actitudes al riesgo de la demanda - Mac Kee Neme, Henry Steve (2020)
The objective of this research is to determine the degree of influence of socioeconomic factors and the risk aversion in the possession and use of credit cards in Peru. The data of the National Survey of Demand for Financial Services and Level of Financial Culture in Peru of 2016, developed by the Superintendencia de Banco, Seguros y AFP del Perú, were used to estimate Tobit models for the study variables; Possession and Use of credit cards. The results prove the significance of studying socioeconomic variables, as sex, age, monthly income, educational level and geographic area are determining factors for the use and possession of credit cards in the country. Also, it prove that having brick or cement block walls, having electricity in the home, and having other accounts in the financial system increase the possession and use of cards. On the other hand, rick aversion does not explain the use or possession of credit card consumers, which would prove that people could have credit cards by necessity or requirement and not by their own decision. However, the degree of influence of these variables on the possession and use of credit cards is low, which is determined by the low results of the probabilistic analysis.